Industry 4.0: An Indian Perspective - Jamwal A.; Agrawal R.; Sharma M.; Pratap S. (My University, 2025)
Industry 4.0 technologies have changed the manufacturing trends in global industries. Industries are adopting Industry 4.0 business models to complete mass customized demands and to compete with global industries. Industry 4.0 can be considered as the current trend of data exchange in manufacturing processes and automation. In India, Industry 4.0 is in its initial stages where the terms digitalization and Industry 4.0 are more widely accepted than fourth industrial revolution. The research work on Industry 4.0 is still limited in India. However, the Government of India has launched some policies and initiatives related to Industry 4.0 and its technologies. The main aim of this paper (1) to provide the more depth insight about the Industry 4.0 and similar terms. (2) to suggest the policies related to India for the transition to Industry 4.0. Indian industries should consider the Industry 4.0 practices seriously as they are shifting their business models from traditional to Industry 4.0 business models. Some issues related to Industry 4.0 implementation like cyber security, machine-to-machine interaction, reliability and stability of CPS should be considered in a better way. In this paper we have discussed about the different initiative by Government of India related for Industry 4.0 technologies. There is need to work on (1) Initiatives related to high investments and technological developments in SMEs and MSMEs industry sectors (2) Identification of infrastructure facilities required for Industry 4.0 and current readiness score of industries. (3) Initiatives related to awareness about Industry 4.0 benefits for industries as well as society. © 2021, IFIP International Federation for Information Processing.